Bivalent copper ions presence triggers removal and homeostatic mechanisms in the metal-resistant microorganism Apiotrichum loubieri M12 - Bonilla, José Oscar (2022)
Microorganisms, especially those habiting mining environments, are of great importance for the retention of toxic metals in the environment. This work aimed to isolate a copper removing-microorganism from sediments of an Acid Mine Drainage-affected environment and to study the cellular responses trigger by metal presence. Apiotrichum loubieri M12 was able to tolerate and remove Cu(II) from liquid culture media, reaching a 30–35% removal capacity when it was exposed to 40 μg mL−1 Cu(II) after 48 h. Analysis of the biomass exposed to the metal through SEM-EDS showed copper presence on the cell surface and variations in the proportion of other biomass constituent elements. Proteomics revealed that the presence of Cu(II) induces differential expression of intracellular proteins involved in a wide variety of metabolic processes. Interestingly, a specific response to the metal was detected in cell-free supernatants, in which copper binding proteins were identified. A large number of proteins with metal ion binding sites were detected both at intra and extracellular levels. The microorganism responds not only by adjusting intracellular protein expression, but also by adjusting expression of proteins in the extracellular space.